An investigation of joint tissue derived stem cells for articular cartilage tissue engineering - Vinardell, Tatiana (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2011)
Tissue engineering has emerged as a promising approach to repair damaged articular cartilage. The associated drawbacks with the isolation and expansion of chondrocytes from autologous tissue have prompted significant research into alternative cell sources such as mesenchymal stem cells (MSCs). Such stem cells have been found in numerous tissues in the body, including bone marrow, periosteum, adipose tissue as well as joint tissues such as infrapatellar fat pad and synovial membrane. In this thesis it was hypothesized that stem cells isolated from within the synovial joint would possess a superior potential to generate phenotypically stable functional cartilaginous tissues compared to other stem cell sources.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin